Antimicrobial Resistance in developing Asian countries: burgeoning challenge to global health security demanding innovative approaches - Rajesh Bhatia (University of New South Wales, 2019)
Antimicrobial resistance (AMR) has been recognized by global leadership as the biggest - and the harshest challenge to the economic development of the humanity and the global health security. Factors responsible for burgeoning AMR are well known. Possible avenues for rapid containment of this scourge have also been articulated. Huge resources -both financial and technical are needed by the developing countries. In the absence of these, innovative cost-effective approaches are needed. Universal health coverage, and One Health approach that brings together human health, animal health and environmental impact to benefit health should be considered by resource-limited countries to implement in their countries with appropriate modifications that provide them with the best outcomes for their populations by preserving efficacy of currently available and affordable antimicrobial agents against infectious diseases.